CORRELATION OF LIVER STIFFNESS MEASUREMENT VIA TRANSIENT ELASTOGRAPHY WITH THE GRADE OF ESOPHAGEAL VARICES IN CIRRHOTIC PATIENTS: A CROSS-SECTIONAL STUDY FROM A TERTIARY CARE CENTER IN NORTH INDIA (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Non-invasive assessment of esophageal varices (EV) is crucial to reduce the burden of screening endoscopies. Methods: A cross-sectional study of 50 patients with chronic liver disease was conducted at GMC Anantnag. Patients underwent FibroScan (LSM and CAP), abdominal ultrasonography, and Esophagogastroduodenoscopy (EGD). MELD and Child-Pugh scores were calculated. Results: MASLD (Metabolic Dysfunction-Associated Steatotic Liver Disease) was the leading etiology (62%). Mean Liver Stiffness Measurement (LSM) was significantly higher in patients with severe varices (52.8 kPa) compared to those without varices (19.8 kPa) ($p < 0.001$). Spleen size and MELD scores showed a linear positive correlation with variceal grade. Conclusion: LSM and clinical scoring systems (MELD/CTP) are robust predictors of EV grade and can serve as effective triage tools for endoscopic intervention.